Power distribution network planning method and device based on new energy access, terminal equipment and storage medium - YI YANG; XU ZHANPENG; MIAO LU; CHEN KUIYE; YANG CHENG; GU YICAN; ZHANG XINGZI; LIU HAOYI; YANG ZHENNAN (2025)
The invention discloses a new energy access-based power distribution network planning method and apparatus, a terminal device and a storage medium. The method comprises the steps of obtaining node data, line data, operation data, new energy basic data, network frame cost data and environmental pollution data of a to-be-planned power distribution network; constructing a power distribution network planning model according to the node data, the line data, the operation data and the new energy basic data; performing calculation according to the node data, the line data, the operation data, the net rack cost data and the environmental pollution data to obtain comprehensive loss cost; solving the power distribution network planning model to obtain power distribution network optimization parameters by taking the minimum comprehensive loss cost as a target under the constructed power grid power flow constraint, power grid voltage constraint, branch current constraint and newly-added network frame line constraint; and